The potential of serum and salivary interleukin-1β and matrix metalloproteinase-8 as determinants of periodontitis grading - Erensu Uzar; Nilgun Gurbuz; Zeynep Akpınar; Malik Ergin; Özgür Koşkan; Zuhal Yetkin Ay (BMC Oral Health)
Abstract Background The aim of this study was to test the hypothesis that salivary and serum interleukin (IL)-1β and matrixmetalloproteinase (MMP)-8 levels, whole blood parameters, and anthropometric measurements, when used alongside the clinical and radiographic parameters used in the current classification, can successfully classify periodontal health status, and grade in periodontitis patients. Methods Two-hundred and forty voluntary individuals were included. Eight groups were constituted: clinical gingival health and gingivitis (on intact and reduced periodontium) and periodontitis (stages I-IV, sub grouped according to grades). Clinical, socio-demographic and anthropometric parameters were recorded. Complete blood and lipid profile analysis were made in serum. Salivary and serum IL-1β and MMP-8 levels of 160 individuals were analyzed with Enzyme Linked Immunosorbent Assay (ELISA). Statistical analyses include Multivariate Analysis of Variance (MANOVA), discriminant analysis, factor analysis and canonical correlation analysis using SPSS v.23® (p < 0.05). Results Seven variables among which serum MMP-8 were found to discriminate the periodontal status with the overall success rate 86.9%. Maximum probing depth and salivary IL-1β have discriminated the grade for periodontitis patients 75%. The factor loading greater than 0.5 included eight variables among which serum IL-1β and serum MMP-8. The clinical and biochemical variables set explain each other 37.82% and 14.38%, reciprocally. Conclusions The results of our study suggest that salivary and serum levels of IL-1β and MMP-8 may serve as potential biomarkers for distinguishing between different grades of periodontitis. Further research is warranted to confirm their diagnostic value and explore their role in periodontal disease progression.